2016
DOI: 10.1108/jhtt-11-2015-0042
|View full text |Cite
|
Sign up to set email alerts
|

Social factors affecting students’ acceptance of e-learning environments in developing and developed countries

Abstract: Purpose The purpose of this study is to propose a conceptual model investigating the impacts of three social factors (i.e. interpersonal influence, external influence and instructor influence) on students’ intention to use e-learning in two different countries: Egypt as an example of a developing country and the UK as an example of a developed country. Design/methodology/approach The subjects of this study were hospitality and tourism students enrolled in “technology-enhanced” courses that were augmented usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
16
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 28 publications
8
16
2
2
Order By: Relevance
“…However, the instructor's communication, responsiveness, and attitude toward the e-learning system did not affect students' usage of the system. This result contradicts prior studies where support was found on the relationship between the instructor and usage or intention to use the e-learning system (Abbas, 2016;Lee et al, 2009;Nair et al, 2015). However, it is consistent with Zhao et al (2019) where no support was found between instructor and continued use intention.…”
Section: Discussioncontrasting
confidence: 95%
“…However, the instructor's communication, responsiveness, and attitude toward the e-learning system did not affect students' usage of the system. This result contradicts prior studies where support was found on the relationship between the instructor and usage or intention to use the e-learning system (Abbas, 2016;Lee et al, 2009;Nair et al, 2015). However, it is consistent with Zhao et al (2019) where no support was found between instructor and continued use intention.…”
Section: Discussioncontrasting
confidence: 95%
“…Moreover, including information on who is sponsoring the survey and offering a phone number for participants to call and verify the survey source may help improve participation. Our findings are similar to others who have explored acceptance of e-interventions such as students’ use of e-learning platforms [37] and the general population’s use of e-banking [38]. The use of financial incentives has been found to increase the behavioral intentions of students, farmers, and the general population to adopt a new technology [39-41].…”
Section: Discussionsupporting
confidence: 89%
“…With the adoption of TAM, the critical factors for the acceptance of E-learning had been identified by several researchers [24,[54][55][56][57][58][59][60][61][62]. Regarding this study, the goal was to analyze the E-learning acceptance behavior of the UAE University students, through whom, better understandings of implications to implement E-learning systems in UAE universities successfully could be gained.…”
Section: Determinants Of Students' Acceptance Of E-learning"mentioning
confidence: 99%